Developing an intervention to promote young people's participation in asthma review consultations with practice nurses. (11th April 2012) - Milnes, Linda J.; McGowan, Linda; Campbell, Malcolm; Callery, Peter
Abstract Aim. The article is a report of a study to develop an evidence‐based pre‐consultation guide for young people to use prior to an asthma review with a practice nurse. Background. The participation of young people aged 13–19 in consultations with health professionals can be limited by the lack of opportunity to learn the appropriate skills in triadic consultations. Evidence‐based interventions to promote participation of adults in consultations have been developed but young people's needs have not been specifically addressed. Design. Multiple methods design informed by guidelines for the development of complex interventions. Methods. A pre‐consultation guide for young people was developed in 2007 by application of a model of health behaviour change, development of criteria by an expert panel and in consultation with young people using a nominal group technique. Results. The concepts of the Health Action Process Approach model were applied to the development of criteria underpinning the pre‐consultation guide. In the nominal groups young people agreed that they had different needs to other children and adults. The consensus was that the preconsultation guide should include disease‐specific information, realistic photographs rather than Clip Art, consistent styles of fonts, bullet points and colours, short words and mature language. Statements and example questions written by young people were included in the evidence‐based guide. Conclusion. Young people's views can contribute to the development of interventions designed to promote communication in consultations with nurses. There is potential for this approach to be used to develop interventions in primary and secondary care of a range of long‐term conditions.